Project Based Learning Model Assisted by STEM Teaching Materials on Students' Critical Thinking Skills - ulil, Muhammad ulil absor; Bambang Subali; Barokah Isdaryanti (Universitas Negeri Semarang, 2024)
This research aims to see the effect of the project-based learning model assisted by STEM teaching materials on students' critical thinking skills. The type of research used is experimental research with pretest and posttest group design. The population and subjects in this research were 4th grade students at MI Ma'arif NU Tamansari, totaling 42 students, with details of 21 students as the experimental class and 21 students as the control class. The data collection technique was carried out by conducting a critical thinking skills test. The activity began with a pretest in both the experimental and control classes, then continued by giving treatment to the experimental class with a project-based learning model assisted by STEM teaching materials and the control class with a discovery learning model assisted by conventional teaching materials. The activity ended by conducting a posttest in both the experimental class and the control class. The results of the pretest and posttest data are then processed by carrying out normality tests and homogeneity tests as prerequisite tests. The results of the normality and homogeneity tests show that the data is normally and homogeneously distributed. Next, data analysis was carried out by making decisions using the paired sample t test and the independent t test. The results of the paired sample t test and the independent sample t test show a significance value of 0.000 < 0.05 so it can be interpreted that the use of the project-based learning model assisted by STEM teaching materials and the discovery learning model assisted by conventional teaching materials has an influence and difference in the average skill results. students' critical thinking. The posttest results in the experimental class averaged 86.95 > 65.71 compared to the average posttest results in the control class so it can be concluded that the use of the project-based learning model assisted by STEM teaching materials has a more significant effect on students' critical thinking skills.